PENGEMBANGAN MULTIMEDIA INTERAKTIF BERBASIS COGNITIVE LOAD THEORY PADA MATA PELAJARAN INFORMATIKA KELAS X SMA - Saputra, Rafiko; Abna Hidayati; Mutiara Felicita Amsal; Rahmi Pratiwi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Informatics learning in the Merdeka Curriculum, particularly within the elements of Data Analysis (AD) and the Social Impact of Informatics (DSI) for Phase E (Class X), contains abstract, dense, and complex concepts that integrate computational logic and cyber law (UU ITE). This conceptual density often triggers cognitive overload in students' working memory, resulting in suboptimal learning engagement and outcomes. This study aims to develop a valid, practical, and instructionally sound interactive multimedia application based on Cognitive Load Theory (CLT) using Articulate Storyline. This research applies the Research and Development (R&D) method with the 4D development model (Define, Design, Develop, and Disseminate). The application incorporates explicit CLT principles: segmenting (breaking topics into learner-paced steps), modality (deploying Text-to-Speech AI narration to balance visual processing), and signaling (applying visual highlights to critical concepts). Data collection instruments comprised needs analysis forms, expert validation sheets, and practicality questionnaires filled out at SMAN 13 Padang. The empirical findings revealed that the multimedia validity reached 4.80 from material experts and 4.42 from media experts, both falling into the